2019
DOI: 10.1038/s41416-019-0429-2
|View full text |Cite
|
Sign up to set email alerts
|

p53 expression status is associated with cancer-specific survival in stage III and high-risk stage II colorectal cancer patients treated with oxaliplatin-based adjuvant chemotherapy

Abstract: BACKGROUND: We attempted to elucidate whether p53 expression or TP53 mutation status was associated with cancer-specific survival in adjuvant FOLFOX-treated patients with stage III or high-risk stage II colorectal cancer (CRC). METHODS: We analysed CRCs (N = 621) for the presence of TP53 alterations and for p53 expression, using targeted resequencing and immunohistochemistry. CRCs were grouped into four subsets according to the p53 expression status, which included p53-no, mild, moderate and strong expression.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 45 publications
(53 reference statements)
5
27
0
Order By: Relevance
“…Although the finding did not achieve statistical significance due to the small cohort size, there are several pieces of additional evidences in the literature for consideration. For example, a recent publication, Oh et al 24 has found a low-expression of TP53 protein was associated with poor cancer-specific survival in Stage III and high-rick Stage II CRC patients (N = 621) who were treated with oxaliplatin-based adjuvant chemotherapy. Additionally, using the TCGA cohort, we found TP53 copy number loss were significantly associated with lower mRNA expression level (P < 1e-15, one tailed T-test on Z-normalized mRNA expression levels, see Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although the finding did not achieve statistical significance due to the small cohort size, there are several pieces of additional evidences in the literature for consideration. For example, a recent publication, Oh et al 24 has found a low-expression of TP53 protein was associated with poor cancer-specific survival in Stage III and high-rick Stage II CRC patients (N = 621) who were treated with oxaliplatin-based adjuvant chemotherapy. Additionally, using the TCGA cohort, we found TP53 copy number loss were significantly associated with lower mRNA expression level (P < 1e-15, one tailed T-test on Z-normalized mRNA expression levels, see Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Although not all abnormal p53 IHC patterns is caused by TP53 mutation, the fact that all the 3 abnormal p53 IHC patterns were signi cantly associated with T2DM in the present study was highly suggestive for a link between T2DM and TP53 mutation. In a recent study [26], the rate of TP53 nonsynonymous SNVs (mutation) were found in 80.2% of p53-strong expression group (> 50% of tumor cells were positive), while rates of stop-gain mutation and indels were found in 38.2% and 14.7% of p53-no group (complete absence) of CRC. In another study using 20% as cut-off value for p53 positive [27], TP53 mutation was found in 79.6% (39/49) of p53 positive CRC and 97.4% (38/39) of the mutation was missense mutation.…”
Section: Discussionmentioning
confidence: 91%
“…Although the finding did not achieve statistical significance due to the small cohort size, there are several pieces of additional evidences in the literature for consideration. For example, a recent publication, Oh et al 24 has found a low-expression of TP53 protein was associated with poor cancer-specific survival in Stage III and high-rick Stage II CRC patients (N=621) who were treated with oxaliplatin-based adjuvant chemotherapy. Additionally, using the TCGA cohort, we found TP53 copy number loss were significantly associated with lower mRNA expression level (P<1e-15, one tailed T-test on Z-normalized mRNA expression levels, see Figure S3).…”
Section: Discussionmentioning
confidence: 99%